A comparative study of the Angono and Cainta municipal libraries (Angono, Rizal and Cainta, Rizal). - Abubakar, Jhoanne C. (2009)
Public libraries play an indispensable role as community centers for information, education, and culture. However, public libraries are unevenly developed especially in developing countries like the Philippines. These usually fail in satisfying the needs of the majority of the users due to the lack of updated materials, the root of which is the small budget allocated. This is a common scenario in the public libraries of Angono and Cainta, both of which are located in the province of Rizal. The status and condition of the two libraries must be taken into account. This includes the libraries' collection, services, physical facilities, and personnel. The strengths and weaknesses of the libraries' components must also be taken into consideration. The researcher used questionnaires, interviewed the municipal librarians and library aides, and conducted observations of the activities inside the libraries. The two libraries were compared in three ways: 1) the contents of their annual statistical reports, 2) their compliance with the Minimum Standards for Public Libraries in the Philippines (MSPP), based on their questionnaires, interviews and observations, 3) observation of each library within its own environment and the results of the users' survey. Despite lacking some of the provisions of the MSPP, the two institutions are still fulfilling their functions as public libraries. The Cainta Municipal Library has complied more with the standards, but the users of Angono Municipal Library are more satisfied with the services of their library.